2010
DOI: 10.1590/s0104-66322010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Including dissolved oxygen dynamics into the Bt δ-endotoxins production process model and its application to process control

Abstract: -This paper proposes a model to characterize the Dissolved Oxygen Dynamics (DO) for the Bacillus thuringiensis (Bt) δ-endotoxins production process. The objective of this work is to include this dynamics into a phenomenological model of the process in order to facilitate the biomass estimation from the knowledge of oxygen consumption; and for control purposes, by allowing the addition of a new control variable in order to favorably influence the bioprocess evolution. The mentioned DO model is based on first pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
0
19
0
3
Order By: Relevance
“…For K L a equal to 13.3 h -1 , growth continued after the dissolved oxygen concentration reached a value of 0 % (Figure 2). It is well known that the oxygen demand of Bacillus thuringiensis decreases during sporulation (Amicarelli et al, 2010) but in these aeration conditions, the oxygen uptake rate (OUR) reached a maximum value of 3.2 mmol/L.h after 8 h of fermentation ( Figure 1d) and the microscopic observation showed that there was no notable fall of the OUR until maturation of most of the spores. This suggests that an oxygen transfer rate of 3.2 mmol/L/h is critical for the sporulation of "Lip" in the process conditions employed, and could explain the defective sporulation for K L a of 7.2 h -1 where the maximal oxygen transfer rate is 1.7 mmol/L/h.…”
Section: Resultsmentioning
confidence: 97%
“…For K L a equal to 13.3 h -1 , growth continued after the dissolved oxygen concentration reached a value of 0 % (Figure 2). It is well known that the oxygen demand of Bacillus thuringiensis decreases during sporulation (Amicarelli et al, 2010) but in these aeration conditions, the oxygen uptake rate (OUR) reached a maximum value of 3.2 mmol/L.h after 8 h of fermentation ( Figure 1d) and the microscopic observation showed that there was no notable fall of the OUR until maturation of most of the spores. This suggests that an oxygen transfer rate of 3.2 mmol/L/h is critical for the sporulation of "Lip" in the process conditions employed, and could explain the defective sporulation for K L a of 7.2 h -1 where the maximal oxygen transfer rate is 1.7 mmol/L/h.…”
Section: Resultsmentioning
confidence: 97%
“…Earlier works demonstrated that in Bt cultures oxygen uptake rates are very high during the vegetative growth, falling drastically after the beginning of the transition phase and maintaining a decreasing profile until the end (Rowe et al 2003;Yezza et al 2005;Berbert-Molina et al 2008;Amicarelli et al 2010). Indeed, some authors verified that lower aeration rates in the sporulation phase, in relation to those employed in the earlier stages of growth, led to a greater toxicity in Btk cultures (Ghribi et al 2007a).…”
Section: Resultsmentioning
confidence: 98%
“…Afterward, Amicarelli et al . improved the model process by adding the DO dynamics due to its importance in the biomass estimation problem and the posterior process control. The DO dynamic model is based on unstructured and unsegregated descriptions of the cell population.…”
Section: Bacillus Thuringiensis δ‐Endotoxins Production Processmentioning
confidence: 99%
“…The following state‐space model is the discrete time version of the continuous‐time counterpart developed by Amicarelli et al centercenternormalXnormalvk+1centerXsk+1centerSk+1centerDOk+1=centercenterμkkskkekTs+1XvkcenterkskXvkTs+XskcenterμkYxtrue/s+msXvkTs+SkcenterK1K2TsX(k)K1Xk+1+DOk+K3QATsDO*DOkwhere X v is the vegetative cell concentration, X S the sporulated cell concentration, X = X v + X S is the total cell concentration ( X (k + 1) =(μ(k) ‐ k e (k))TsX v (k) + X(k)), S is the limiting substrate concentration, and DO is the DO concentration.…”
Section: Bacillus Thuringiensis δ‐Endotoxins Production Processmentioning
confidence: 99%